Behaviour of Masonry-Infilled RC Frames Strengthened Using Textile Reinforced Mortar: An Experimental and Numerical Studies Overview - Filippou, Christiana; Furtado, André; De Risi, Maria Teresa; Kyriakides, Nicholas; Chrysostomou, Christis (My University, 2022)
A large part of the existing building stock was not designed according to the current codes in seismic prone regions. The poor performance of some reinforced concrete structures was related to the presence of the masonry infill walls. Although the infill walls can increase the lateral resistance of frames in many cases, it is widely recognized that there is a high vulnerability of the masonry infill walls subjected to loadings along and perpendicular to their plane. Several collapses were observed after past earthquakes in infilled frame buildings. For this reason, different retrofitting design approaches have been proposed and used during the last years; however, many of them do not fit with the building’s owners’ economic demands or technical knowledge of the workmanship. Over the years, significant research has been conducted for masonry wall elements retrofitted with textile-reinforced mortar (TRM). However, much less has been carried for masonry-infilled frame RC frames. Thus, this manuscript aims to provide a literature review about research on assessing the effectiveness of using TRM technique to reduce masonry-infilled RC frames’ seismic vulnerability. Experimental findings will be deeply analysed to provide full insight concerning the TRM’s efficiency under in-plane and/or out-of-plane demands of infilled frames and some variables such as anchorage of the TRM to the structure. Numerical modelling approaches to simulate the complex behaviour of infilled frames with TRM are also presented to stress their benefits or limits. Covering completely all aspects of this manuscript is essential to briefly describe the studies conducted so far to examine either numerically or experimentally the effectiveness of using TRM for retrofitting masonry wall elements.
Keywords: Experimental tests; Textile-reinforced mortar; Strengthening techniques; Numerical modelling; Masonry infills; Literature review